2020
DOI: 10.3389/fmech.2020.00050
|View full text |Cite
|
Sign up to set email alerts
|

Sdq-Sdr Topological Map of Surface Topographies

Abstract: The reliable characterization of surface topographies-especially in case of tribological processes-requires complex and comprehensive solution methods. The use of a combination of roughness parameters offers effective solutions in many cases. In our study, we found a close correlation between the Sdq-Sdr parameter pair and we applied the two parameters as a topological map. Surface topographies resulting from different machining techniques (turned, milled, ground, honed, electric discharge machined, and sinter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 10 publications
3
14
0
Order By: Relevance
“…The figure 14 therefore shows, without reporting a detailed statistical study in this respect, a fit of the experimental data through the theoretical relationship found, both for ABS and PC-ABS surfaces, independently of the etching process used. Another confirmation of the theoretical relationship found can be obtained for example in [21]. In this cited work, the values of Sdr and Sdq were measured for different surfaces and the best fit correlating these two parameters was calculated: this best fit is therefore a purely empirical relationship, in contrast to the theoretical relationship proposed and shown in equation ( 12), which was obtained through theoretical evaluations.…”
Section: Correlation Of Parameterssupporting
confidence: 58%
See 1 more Smart Citation
“…The figure 14 therefore shows, without reporting a detailed statistical study in this respect, a fit of the experimental data through the theoretical relationship found, both for ABS and PC-ABS surfaces, independently of the etching process used. Another confirmation of the theoretical relationship found can be obtained for example in [21]. In this cited work, the values of Sdr and Sdq were measured for different surfaces and the best fit correlating these two parameters was calculated: this best fit is therefore a purely empirical relationship, in contrast to the theoretical relationship proposed and shown in equation ( 12), which was obtained through theoretical evaluations.…”
Section: Correlation Of Parameterssupporting
confidence: 58%
“…I n the literature, there are many studies on the possible correlation between different morphological parameters of the ISO 25178 standard. This works show that some parameters of this standard often have a correlation for certain types of surfaces [21][22][23]: all studies propose empirical relationships and best fits found through direct measurements on the studied samples, without however proposing theoretical relationships able to explain in detail the experimental evidence. The most studied case is the possible correlation between the Sdq and Sdr hybrid parameters: observing the definitions of these parameters, it is possible to guess a possible correlation between the two, even if the existence of a real analytical correlation between the two definitions is not obvious.…”
Section: Correlation Of Parametersmentioning
confidence: 99%
“…For comparatively smooth surfaces measured with reasonable sampling intervals, only one hybrid parameter is recommended for surface description. Because the Sdq and Sdr parameters are interconnected, the correlation between them is extremely high (for example, Czifra and Baranyi [143] obtained the determination coefficient of 0.998).…”
Section: Hybrid Parametersmentioning
confidence: 99%
“…Because the Sdq and Sdr parameters are interconnected, the correlation between them is extremely high (for example, Czifra and Baranyi [ 143 ] obtained the determination coefficient of 0.998).…”
Section: Hybrid Parametersmentioning
confidence: 99%
“…In confocal microscopic analysis, one can understand the nature of the surface topography of the machined NiTiNOL sample in terms of average height deviations (surface average roughness) (Sa), maximum height of the peak in the entire area under study (Sz), skewness (S sk ) and kurtosis (S ku ). Skewness is the measure of asymmetry of surface deviations about the mean plane and kurtosis is the measure of peakedness of the surface height distribution [22,23]. Sa, Sz, S sk and S ku are considered for the present study, as Sa is required to understand the overall average deviation and Sz, S sk and S ku are important factors for biomedical applications [24,25].…”
Section: Process Variables and Output Responsesmentioning
confidence: 99%